Design of a Stable Heusler Alloy with Switchable Metal‐to‐Half‐Metal Transition at Finite Temperature. Issue 11 (4th October 2021) - Buchelnikov, Vasiliy D.; Sokolovskiy, Vladimir V.; Miroshkina, Olga N.; Baigutlin, Danil R.; Zagrebin, Mikhail A.; Barbiellini, Bernardo; Singh, Bahadur; Bansil, Arun; Lähderanta, Erkki
Abstract: The electronic structure and metallicity of Si‐doped Mn2 VGe Heusler alloys within the first‐principles density‐functional theory framework are discussed. Mn2 VGe is found to assume two stable structures at (cubic) lattice constants of 5.7 and 6.05 Å, which are well‐separated in energy and correspond to half‐metallic (low‐spin) and metallic (high‐spin) phases, respectively. Substitution of Ge by Si reduces the energy difference between these two phases, which become nearly degenerate at an Si concentration of ≈3.125 at% at zero temperature. The analysis shows that the switching between the high‐ and low‐spin phases for this composition can be triggered via a pressure of 2.8 GPa at 300 K. Si‐doped Mn2 VGe can thus provide an ultrafast, low power, cost‐effective materials platform for spintronics applications. Abstract : Using first‐principles modeling, Mn2 VGe is shown to assume two stable structures with different lattice constants, which are well‐separated in energy and correspond to a half‐metallic low‐spin magnetic state (LMS) and a metallic high‐spin magnetic state (HMS). Substitution of Ge by Si atoms decreases the temperature and pressure at which the LMS and HMS can be switched.